Assessing The Thermal Comfort Conditions In Open Spaces: A Transversal Field Survey On The University Campus In India (International Journal of Built Environment and Sustainability, 2021)
Outdoor thermal comfort (OTC) promotes the usage frequency of public places, recreational activities, and people's wellbeing. Despite the increased interest in OTC research in the past decade, less attention has been paid to OTC research in cold weather, especially in arid regions. The present study investigates the OTC conditions in open spaces at the campus area in the arid region. The study was conducted by using subjective surveys(questionnaire) and onsite monitoring (microclimate parameters). The study was conducted at the Deenbandhu Chhotu Ram University of Science and Technology, Murthal, Haryana-India campus during the cold season of 2019. The timings of surveys were between 9:00 and 17:00 hours. The authors processed the 185 valid questionnaire responses of the respondents to analyze OTC conditions. Only 8.6% of the respondents marked their perceived sensation "Neutral." Regression analysis was applied between respondents' thermal sensations and microclimate parameters to develop the empirical thermal sensation model. The air temperature was the most dominant parameter affecting the sensations of the respondents. The empirical model indicated that by increasing air temperature, relative humidity, and solar radiation, the thermal sensations also increased while wind speed had an opposite effect. Physiological equivalent temperature (PET) was applied for assessing the OTC conditions; the neutral PET range was found to be 18.42-25.37°C with a neutral temperature of 21.89°C. The preferred temperature was 21.99 °C by applying Probit analysis. The study's findings could provide valuable information in designing and planning outdoor spaces for educational institutions in India's arid regions
Keywords: Outdoor thermal comfort, PET, Thermal sensation vote model, Cold season, Thermal stress